La política en la actualidad : ¿más cerca de la virtud o del vicio? - Rojas, Eugenio Yáñez (Sapientia, 2014)
This article briefly discussed in two very different ways of thinking about politics, namely that of some classic authors, whose main representatives are Plato, Aristotle, Cicero and Aquinas, and modern represented by Machiavelli. The first, saving some differences, understand politics as a practical moral knowledge as a noble activity that must be exerted by the best in view of the good of all. Machiavelli, meanwhile, sees it as a technique, totally uprooted morals, whose purpose is to obtain, maintain and increase power. Apparently, and this is what we will try to show in the exhibition, there is enough evidence to state that Machiavellianism was «imposed» on the classics. The perspective from which this question is addressed, is the recent Magisterium of the Catholic Church.